2020
DOI: 10.33448/rsd-v9i8.5198
|View full text |Cite
|
Sign up to set email alerts
|

Compost barns in Brazilian Subtropical region (Part 1): facility, barn management and herd characteristics

Abstract: The objective of this study was to describe barn management practices and to evaluating cow locomotion, hygiene and hock lesion prevalence of dairy cows housed in Compost Barns (CB) located in the subtropical region of Brazil. The CB has demonstrated satisfactory results in relation to animal comfort and productivity. However, modifications to the initial American recommendations are being made by producers in order to adapt it to different conditions. Thirty dairy farms were analyzed regarding structural meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Like our results of body cleanliness ( Table 1 ), a lower prevalence of integument alternations and greater in the dirt was found in cows reared in CB than the FS [ 21 ]. On the other hand, it is essential to consider that management can influence the bedding quality and the dirt score of cows reared in CB [ 13 , 47 ] and, in some cases, may not occur differences in the dirt score between FS and CB [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like our results of body cleanliness ( Table 1 ), a lower prevalence of integument alternations and greater in the dirt was found in cows reared in CB than the FS [ 21 ]. On the other hand, it is essential to consider that management can influence the bedding quality and the dirt score of cows reared in CB [ 13 , 47 ] and, in some cases, may not occur differences in the dirt score between FS and CB [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently the emergence and growth of the CB system has been observed, a still rare system in Brazil, at the time of the mentioned work. The work developed by Radavelli et al [ 13 ] characterized the CB system in the west region of SC, indicating the massive presence of this system in the region in early 2017. In this sense, work is needed to show the impact of the migration from PT production systems to FS and CB on the welfare of dairy cows as it has already been shown that confinement limit the manifestation of the natural behaviors [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Kentucky, USA, Black et al [ 20 ] observed an average ratio of C:N ranging from 16:1 to 35:1. In Brazil, Radavelli et al [ 26 ] found an average ratio of C:N of 10:51. In this context, Shane et al [ 21 ] reported that the highest C:N ratio found was 26.0 during winter.…”
Section: Discussionmentioning
confidence: 99%
“…In kiln-dried sawdust, the particle size distribution was 13.1% in the thinnest material, 8.5% in the material with 2 mm granulometry, 1.0% in the material with 4.75 mm, 3.0% in the material of 5.60 mm, 14.2% in the material of 8.00 mm and 8.1% in the material with larger granulometry (>25.00 mm). In a prior study, Radavelli et al [ 26 ], when evaluating the particle size in the CBP beds, observed that the material present in the bottom of the sieve represented 29.05%, small material (2 mm) 16.08%, medium material (4.75 mm) 18.36% and large material (9.75 mm) 32.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation